Effects of scapular stabilization exercise on neck posture and muscle activation in individuals with neck pain and forward head posture - Im, Boyoung (J Phys Ther Sci, 2016)
[Purpose] The purpose of this study was to investigate the effects of scapular stabilization exercise on neck posture, muscle activity, pain, and quality of life in individuals with neck pain and forward head posture. [Subjects and Methods] Fifteen participants were recruited according to the selection criteria and were randomly allocated to the scapular stabilization group (n=8) and the control group (n=7). The scapular stabilization group underwent training for 30 minutes a day, 3 times a week for 4 weeks; the control group performed relaxation exercises for 4 weeks. [Results] After training the scapular stabilization group showed significant improvement on the craniovertebral angle, upper trapezius muscle activity, serratus anterior muscle activity, Neck Disability Index scores, Visual Analog Scale scores, and World Health Organization Quality of Life Assessment-BREF scores compared to those in the control group. [Conclusion] Scapular stabilization exercise can help improve the head posture and pain in the patients with neck pain and forward head posture. Controlling the muscular activities through scapular stabilization exercise also improves the patients’ quality of life.